Study on Microstructure and Properties of CrFeCoNiTix High-Entropy Alloy - JIANG Yue; ZHOU Guang-tai; CHENG Si-meng; LI Xiu-ming (Journal of Harbin University of Science and Technology)
In order to study the variation of Ti content on the microstructure and properties of the high entropy entropy alloy was analyzed by XＲD，SEM，EDS and metallographic microscope. The micro Vickers hardness of the high － entropy alloy was tested with Vickers hardness tester． The electrochemical corrosion performance of CrFeCoNiTix high － entropy alloy in 3. 5wt% NaCl solution was also studied． The results showed that CrFeCoNiTix high － entropy alloy was mainly composed of FCC phase structure． With the increase of Ti element addition，the lattice distortion of the high － entropy alloy increases，and the solid solution phase ( B phase，L phase) in the interdendritic area gradually increases． And the high － entropy alloy was transformed from single － phase structure to dendrite and interdendrite two － phase structure due to the increase of Ti element addition amount． The dendrite area of the alloy is rich in Fe，Co，Ni elements，the interdendritic area is rich in Ti element，and the Cr element is more evenly distributed in the alloy matrix． The vickers hardness value of the alloy showed a gradually increasing trend with the increase of Ti content． When x = 1. 0，the hardness of the alloy reached the maximum value of 643. 8 HV． CrFeCoNiTi0. 6 high － entropy alloy has better corrosion resistance